The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/ijms22010422
|View full text |Cite
|
Sign up to set email alerts
|

Tear Proteomics Study of Dry Eye Disease: Which Eye Do You Adopt as the Representative Eye for the Study?

Abstract: Most studies about dry eye disease (DED) chose unilateral eye for investigation and drew conclusions based on monocular results, whereas most studies involving tear proteomics were based on the results of pooling tears from a group of DED patients. Patients with DED were consecutively enrolled for binocular clinical tests, tear biochemical markers of DED, and tear proteome. We found that bilateral eyes of DED patients may have similar but different ocular surface performance and tear proteome. Most ocular surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
(18 reference statements)
0
11
1
Order By: Relevance
“…Kuo et al mentioned in their recently published research that bilateral eyes of DED patients may have similar but different ocular surface performance and tear composition [28]. Similar to the research of other authors in our study results, we included the first examined eye because automatic measurement may produce distorted measurements and results from the second examined eye [28,30].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Kuo et al mentioned in their recently published research that bilateral eyes of DED patients may have similar but different ocular surface performance and tear composition [28]. Similar to the research of other authors in our study results, we included the first examined eye because automatic measurement may produce distorted measurements and results from the second examined eye [28,30].…”
Section: Discussionmentioning
confidence: 75%
“…There were no statistically significant differences between the eyes. The automatic measurement may produce distorted results for the other eye; therefore, in our results we included only the first eye examined [28].…”
Section: Examinationsmentioning
confidence: 99%
“…It was recommended to evaluate the biochemical features of tears in DED from the more severe eye [ 49 ]. Also, the more severe eye may reflect the ocular discomfort better.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, DED has been considered a disease of multifactorial etiology, and is correlated to the presence of certain comorbidities in systemic organs 7 . DED etiology and pathology findings have indicated that patients with different DED etiologies may present with different signs and symptoms 8 . It has been reported that patients who smoke or have comorbidities experience more severe symptoms of DED, when compared to patients in a control group 9 .…”
Section: Background and Summarymentioning
confidence: 99%